Impact of Supplier Relationship on Service Delivery - Roba Sarah Emmanuel (Uganda Christian University, 2023)
This research report, titled "Impact of supplier relationship management on service delivery" aims to assess the effect of alliance relationship on service delivery in Shipax Africa Ltd, to examine the impact of collaborative supplier relationship management on service delivery of Shipax Africa Ltd and to examine the extent of adversial supplier relationship management on service delivery performance of Shipax Africa Ltd. The study delves into supplier relationship management and service delivery, utilizing qualitative and quantitative method of research Throughout the research process, transportation costs, not getting all the data need from the respondents, which should be considered when interpreting the results. Future research in this area could find out effects of supplier relationship on the product quality and examine the effects of supplier development on the supplier performance. This research contributes to the existing body of knowledge on the Impact of Supplier relationship management on service delivery and offers valuable insights for Shipax Africa Ltd It serves as a valuable resource for academics, practitioners, and policymakers interested in.
This is a dissertation.